The influence of hypoglycemia on the specific quality of life in type 2 diabetes mellitus: a comparative cross-sectional study of diabetics with and without hypoglycemia in Xi’an, China - Chao Wu (Health and Quality of Life Outcomes, 2021)
Abstract Purpose This study aims to explore the incidence of hypoglycemia in patients with type 2 diabetes mellitus (T2DM) and the influence of hypoglycemia on the specific quality of life in T2DM patients. Methods It was a comparative cross-sectional study consisting of 519 T2DM patients in Xi'an, China and patients were investigated by self-reported hypoglycemia and specific quality of life questionnaires from September 2019 to January 2020. Descriptive analysis, t-test, Chi-square test, hierarchical regression analysis and stepwise multiple regression analysis were applied to assess the influence of hypoglycemia on the specific quality of life. Results The incidence of hypoglycemia in T2DM patients was 32.18%. The mean score of specific quality of life in diabetes without hypoglycemia was 57.33 ± 15.36 and was 61.56 ± 17.50 in those with hypoglycemia, which indicated that hypoglycemia had a serious impact on the quality of life of diabetics (t = − 5.172, p = 0.000). In the Univariate analysis of specific quality of life, age, education background, marital status, living status, duration of diabetes, monthly income per capita were independent and significant factors associated with specific quality of life of two groups of T2DM patients (p < 0.05). In the hierarchical regression analysis, the duration of the diabetes more than 11 years and the frequency of hypoglycemia more than 6 times in half a year entered the equation of specific quality of life of 519 diabetics respectively (p < 0.001). In multiple linear regression analysis, age, marital status and income all entered the regression equation of quality of life of the two groups (p < 0.05). Conclusion Hypoglycemia will have a serious impact on the quality of life of T2DM patients. In order to improve the living quality in diabetics, effective measurements should be taken to strengthen the management of blood glucose and to avoid hypoglycemia.